Genetic Evaluation of Growth and Survival-Related Traits in Yesso Scallop Patinopecten yessoensis in Sea-Based Culture System - Wu, Fucun; Liu, Chao; Zhang, Jibiao; Zhang, Guofan (Frontiers in Marine Science, 2022)
Worldwide, bivalve aquaculture industry has realized or recognized the potential gains from selective breeding programs using phenotypic and pedigree data. Yesso scallop Patinopecten yessoensis are among the most important commercial shellfish in China. A family-based breeding program to investigate the genetic variations for growth and survival related traits at suspended and bottom environments of sea-based culture system was reported in this study. We proposed and conducted a novel phenotyping technique to longitudinally evaluate the shell heights in yesso scallop. At harvest after rearing for 20 months, the individual shell heights at 6, 10, 16 and 20 months were simultaneously obtained by the growth rings in the outer shells of the animals. Meanwhile, the body weight of the survived individuals at harvest were also recorded. Variance components and genetic parameters for growth and survival related traits were estimated using an animal and threshold model, respectively. At the suspended environment, the heritability estimates for body weight and shell heights at specific ages ranged from moderate to high (0.328 to 0.853). The estimated correlations between shell heights at contiguous ages were consistently high, ranging from 0.890 to 0.958, but decreased with increasing interval between ages (0.496-0.828). The estimated correlations between shell heights at contiguous ages and body weight at harvest were similar, ranging from 0.535 to 0.983. The heritability estimates for individual survival at harvest were at a low level of 0.128 by the probit-threshold model. While at the bottom environment, estimates of heritability for growth and survival related traits were similar but slight lower than those at the suspended environment. Further, the genetic correlation for body weight between the two environments was very small, which probably indicating genotype by environment interaction effects for growth in yesso scallop. The study can provide prior information, which might develop new idea for selection in this species. The results are discussed in relation to selection work with yesso scallop, and solutions for accurate estimation of genetic parameter and increasing genetic gain are also outlined.